ҚИЗИЛҚУМДА СОДИР БЎЛГАН ИҚЛИМ ЎЗГАРИШЛАРИ ВА УНИНГ ОҚИБАТЛАРИ - Жалилов, М.Б. (SCIENCE and SOCIETY, 2024)
This article talks about the nature and climatic conditions of the Kyzylkum desert, which has been inhabited by mankind since ancient times. It is known that since time immemorial mankind has been struggling to live in any conditions. The article reveals that this process is especially difficult in the desert region with hot summers and harsh winters. Climate change is said to be the factor that has the strongest impact on farm characteristics. During the article, information is given about the negative consequences of environmental problems, especially the increased level of desertification.